Variation in structure and properties of poly(glycerol adipate) via control of chain branching during enzymatic synthesis - Taresco, Vincenzo; Creasey, Rhiannon; Kennon, J.; Mantovani, Giuseppe; Alexander, Cameron; Burley, Jonathan C.; Garnett, Martin C. (Elsevier, 2016)
Poly (glycerol adipate) (PGA) can be produced from divinyl adipate and unprotected glycerol by an enzymatic route to generate a polymer with relatively low molar mass (12 kDa). PGA bears a pendant hydroxyl group which imparts a hydrophilic character to this water insoluble polymer. We have examined the effect of synthesis temperature on polymer characteristics through various techniques including FT-IR, 1H and 13C NMR, surface and thermal analysis, both to expand the data already present in the literature about this material and to understand better its properties for potential pharmaceutical applications. The use of a lipase (Novozym 435) as a catalyst suppresses cross-linking at the pendant glyceryl hydroxyl through steric hindrance at the active site, thus producing polymers with low degrees of branching (5–30%), and removes the need for any pre- or post-polymerization protection/deprotection reactions. Careful temperature control during synthesis can give polymers with reproducible molecular weights and reduced amounts of polymer branching compared to synthesis at higher temperatures. Due to the ability of the synthetic route to produce a range of structures, PGA generated by enzymatic routes may emerge as a useful biodegradable polymer platform to engineer solid dispersions or nanoparticles for healthcare applications.